Implementasi Kebijakan Pembangunan Pembangkit Listrik Tenaga Surya Terpusat di Daerah Permukiman Wilayah Pesisir Kota Bontang - Hassanal Ikrom Jamil; Nuraisyah; Ani Susanti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study examines the implementation of centralized Solar Power Plant (PLTS) development policies in the coastal area of Bontang City as part of efforts to meet the increasing national energy demand. PLTS was chosen due to its renewable, environmentally friendly, and efficient nature, leveraging Indonesia's abundant solar radiation. Using a qualitative approach, the study reviews policy implementation based on the four main dimensions of George C. Edward III's theory: communication, resources, implementers’ disposition, and bureaucratic structure. The findings reveal that communication among policy implementers, the community, and stakeholders has been effective through various formal and informal channels, although challenges remain in disseminating information to remote coastal communities. In terms of resources, facilities and information related to the policy are deemed adequate, but there is a shortage of technical personnel and local operators, impacting policy execution. Additionally, limited government budgets pose a significant barrier to PLTS maintenance and operations. The disposition of implementers reflects strong commitment and responsibility, including the recruitment of local labor as operators, although heavy workloads and equipment theft issues hinder effectiveness. The bureaucratic structure, based on standard operating procedures (SOPs), has supported systematic coordination and policy implementation. Overall, the study concludes that the implementation of centralized PLTS development policies in the coastal area of Bontang City has been relatively effective. However, enhancements in human resources, increased budget allocation, and stricter supervision and facility protection are required. The study recommends closer collaboration among central and local governments, communities, and the private sector to ensure the sustainability of PLTS as an innovative and environmentally friendly energy solution for coastal areas.